Development and validation of HPTLC stability indicating method for estimation of Azilsartan Medoxomil using Fluorescence mode - Santosh V. Gandhi; Vrushpriya H. Habde (International Journal of Pharmacy and Analytical Research, 2016)
Azilsartan medoxomil is an angiotensin II receptor antagonist used in the management of hypertension. A simple, selective, and sensitive High Performance Thin layer Liquid Chromatographic (HPTLC) method for the determination of Azilsartan medoxomil using fluorescence mode has been developed. The HPTLC separation was achieved on the aluminum backed layer of silica gel 60F254 using Toluene: Methanol (8:2 v/v) as mobile phase. Quantification was achieved using fluorescence mode at 312 nm over the concentration range of 200 to 1000 ng/band with correlation coefficient of 0.991.The recovery study results ranged from 99.33- 99.59%for Azilsartan medoxomil. Retention factor (Rf) was found to be 0.38 ± 0.04respectively. The method is simple and was successfully validated according to ICH guidelines Q2 (R1). The method showed acceptable values for assay, accuracy, p recision, robustness, sensitivity and stability.